2020
DOI: 10.1111/jvim.15958
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy of telmisartan for the treatment of persistent renal proteinuria in dogs: A double‐masked, randomized clinical trial

Abstract: Background Information regarding efficacy of the angiotensin II receptor blocker, telmisartan, for treatment of proteinuria in dogs is limited. Objective To evaluate the antiproteinuric efficacy of telmisartan, as compared to enalapril, in dogs with chronic kidney disease and persistent, renal proteinuria. Animals Thirty‐nine client‐owned dogs with chronic kidney disease and urinary protein‐to‐creatinine ratio (UPC) > 0.5 (if azotemic) or ≥ 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 51 publications
(52 reference statements)
2
27
1
Order By: Relevance
“…[20][21][22][23][24][25][26][27][28][29][30][31] A recently published clinical trial in dogs showed that 31% of dogs developed significant increases in SCr requiring hospitalization for treatment, further supporting this argument. 18 Blockade at the angiotensin-II receptors by ARBs could offer a potential benefit over the use of ACEi, especially in dogs refractory to treatment, as was observed in a recent clinical trial. 18 We also cannot exclude that the 2 dogs in our study that had complete response with combination treatment after introduction of telmisartan could have had a similar response had the ACEi been gradually withdrawn or discontinued, as previously described in a case report.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…[20][21][22][23][24][25][26][27][28][29][30][31] A recently published clinical trial in dogs showed that 31% of dogs developed significant increases in SCr requiring hospitalization for treatment, further supporting this argument. 18 Blockade at the angiotensin-II receptors by ARBs could offer a potential benefit over the use of ACEi, especially in dogs refractory to treatment, as was observed in a recent clinical trial. 18 We also cannot exclude that the 2 dogs in our study that had complete response with combination treatment after introduction of telmisartan could have had a similar response had the ACEi been gradually withdrawn or discontinued, as previously described in a case report.…”
Section: Discussionmentioning
confidence: 93%
“…18 Blockade at the angiotensin-II receptors by ARBs could offer a potential benefit over the use of ACEi, especially in dogs refractory to treatment, as was observed in a recent clinical trial. 18 We also cannot exclude that the 2 dogs in our study that had complete response with combination treatment after introduction of telmisartan could have had a similar response had the ACEi been gradually withdrawn or discontinued, as previously described in a case report. 17 Six dogs were treated with both telmisartan and mycophenolate, and a partial or complete response was observed for most of these dogs at the follow-up visits.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The therapeutic management of RF started after CKD staging and substaging (20,22). Patients in stage I of the disease with persistent proteinuria were fed a renal therapeutic diet, 1 and an ACEI or ARA was incorporated to the medical management (13,(22)(23)(24). Patients in azotemic stages received a renal therapeutic diet and a phosphate binder with food every 12 h 2 .…”
Section: Diagnosis Staging and Longitudinal Ckd Monitoringmentioning
confidence: 99%